Modelling trajectories of solid particle motion in the cyclone. Issue 6 (7th August 2017) - Baltrėnas, Pranas; Leonavičienė, Teresė
Abstract : Purpose: This purpose of the paper is to examine the multi-channel cyclone created at the Vilnius Gediminas Technical University (VGTU) Research Institute of Environmental Protection. The paper aims to predict the possible trajectories of solid particle motion in the cyclone with reference to the mechanical forces only. Design/methodology/approach: The numerical calculations were performed on the basis of experimental results. The system of differential equations describing particle motion in the cyclone is analysed and numerically solved using Runge–Kutta–Fehlberg method. Research consists of three examples that illustrate the impact of particle density and velocity on collection and analyses the particle motion trajectories in the first and second channels of the cyclone. Findings: Numerical calculations were performed according to the data from Vilnius Gediminas Technical University Research Institute of Environmental Protection. The particulate matter of wood ash and granite were used. The collection of solid particles of different size was examined when the air inflow velocity varies from 10 to 20 m/s. The possible motion trajectories of the solid particles are defined and the parameters of collected particles have been discussed. Research limitations/implications: The obtained results can be used for the analysis of air cleaning efficiency and particulate matter removal from air in a multi-channel cyclone. Practical implications: The results lead us to improve the structure of the cyclone so as to effectively collect the solid particles of different size. Originality/value: This paper presents the results obtained for the multi-channel cyclone created at the Vilnius Gediminas Technical University Research Institute of Environmental Protection.